2018
DOI: 10.1097/gox.0000000000001829
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Delay Impact on Open Reduction Internal Fixation of Mandibular Fractures: A Systematic Review

Abstract: Background:The impact of mandible fracture treatment delay has been contested in the literature for decades, with conventional wisdom favoring earlier surgical treatment to prevent postoperative complications, primarily infection. Through a systematic review of all available evidence, this study aims to determine whether delay to open reduction and internal fixation of traumatic mandibular fractures influences outcomes.Methods:MEDLINE, EMBASE, CINAHL, and Web of Science were systematically searched for English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…It is consensus that MF should be addressed early, in general, treatment is performed as soon as possible, ideally in the first 72 hours after the traumatic event. However, this timing is at the mercy of many variables, such as urgency in addressing other injuries, age, comorbidities, mental disorders, non-cooperative patients, lack of specialized care, delayed communication and transfer between hospital units, and financial situation (Hurrell & Batstone, 2014;Stone et al, 2018;Kraeima et al, 2018;King et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is consensus that MF should be addressed early, in general, treatment is performed as soon as possible, ideally in the first 72 hours after the traumatic event. However, this timing is at the mercy of many variables, such as urgency in addressing other injuries, age, comorbidities, mental disorders, non-cooperative patients, lack of specialized care, delayed communication and transfer between hospital units, and financial situation (Hurrell & Batstone, 2014;Stone et al, 2018;Kraeima et al, 2018;King et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Patients may report pain, functional limitation, dysphagia, occlusal changes and facial deformities, which is why, in most cases, surgical treatment is necessary (Pickrell & Hollier, 2017). Untreated mandibular fractures (MF) may result in trismus, malocclusion, infection and persistent pain; therefore, they must be addressed early to avoid complications, malunion and nonunion of bone fragments (Stone et al, 2018;Reddy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of well-designed prospective studies to reliably determine the importance of treatment delay as an independent predictor of postoperative complications including nonunion. 3 Additionally, because of the possible serious consequences of infection, it has traditionally been routine to administer postoperative antibiotics. However, in recent years, this has also been questioned.…”
Section: Nonunion and Infectionmentioning
confidence: 99%
“…6), including an orbital systematic review in 2015 and an orbital systematic review and meta-analysis in 2016 (55,78,79,(94)(95)(96)(97)(98). Of note, the 2015 systematic review by Dubois et al(55) included six of the ten case series otherwise identified by this PhD literature review(80,81,84,86,94,97), and the 2016 systematic review and meta-analysis by Daamgard et al(78) identified the review by Dubois et al(55), along with a differing six of ten case series otherwise identified by this PhD literature review (81,84,86,87,95,96).…”
mentioning
confidence: 99%
“….6 Studies identified in 2019 that found a conflicted relationship between treatment delay and treatment outcome.Twenty-seven studies were identified in the literature over the entire review period that analysed outcomes of mandible fracture treatment in isolation with respect to treatment delay. (17, 18, 21, 24, 25, 57-59, 62-65, 68-71, 73-77, 79, 85, 88, 91, 93, 98) Of the twenty-seven, there were twenty-three retrospective case series(17, 18, 24, 57-59, 63-65, 68-71, 73-77, 85, 88, 91, 93, 98), two prospective case series(21,62), and two systematic reviews (25,79). The first systematic review, by Hermund et al in 2008, stated that ''there is presently no strong evidence for either acute or delayed treatment of mandibular fractures in order to minimise healing complications".…”
mentioning
confidence: 99%